Prevalence, Risk Factors of Preserved Ratio Impaired Spirometry in adult in plateau: A Cross-Sectional Study - Junjie Xia; Yu Qiu; Ling Huang; Wenjun Li; Xingxiong Zou; Xiaoqian Wang; Xiaoli Hou; Yuting Chen; Haishi Xue; Runjiao Chen; Lingna Li; Ke Yi; et al. (PLoS ONE, 2025)
Background Preserved ratio impaired spirometry(PRISm) is considered to be a precursor of COPD. The purpose of our study is to investigate the prevalence and risk factors of PRISm in high-altitude areas. Methods The adult residents of Hongyuan County were selected by random sampling method, and the lung function tests, questionnaires, blood tests were conducted. The prevalence of PRISm was compared among different factors of investigation, and binary logistic regression analysis was used to determine the independent influencing factors of PRISm. Results 627 participants qualified for quality control, the prevalence was 10.06%. The independent factors of PRISm were age 40–49 years old(OR = 4.322,95%CI: 1.149–16.262),age ≧ 60 years (OR = 4.453, 95% CI: 1.003–19.762),Body mass index ≧ 30(OR: 3.745, 95% CI: 1.611–8.707),Smoking (OR: 2.591, 95% CI: 1.305–5.146), Diabetes (OR: 3.894, 95% CI: 1.043–14.199), history of pulmonary tuberculosis (OR: 13.678, 95% CI: 5.495–34.049), hypertension(OR: 3.447, 95% CI: 1.529–7.771), White blood cell count(OR: 1.414, 95% CI: 1.164–1.717), and Red blood cell volume distribution width (OR: 1.098, 95% CI: 1.009–1.196). Conclusion The prevalence of PRISm in Hongyuan County was 10.03%; The independent influencing factors of PRISm included age, smoking, the history of tuberculosis, diabetes,hypertension,body mass index ≧ 30,Red blood cell volume distribution width.